2014
DOI: 10.1051/0004-6361/201323349
|View full text |Cite
|
Sign up to set email alerts
|

Herschelobservations of Hickson compact groups of galaxies: Unveiling the properties of cold dust

Abstract: We present a Herschel far-infrared and sub-millimetre (sub-mm) study of a sample of 120 galaxies in 28 Hickson compact groups (HCGs). Fitting their UV to sub-mm spectral energy distributions with the model of da Cunha et al. (2008), we accurately estimate the dust masses, luminosities, and temperatures of the individual galaxies. We find that nearly half of the late-type galaxies in dynamically "old" groups, those with more than 25% of early-type members and redder UV-optical colours, also have significantly l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
66
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(76 citation statements)
references
References 82 publications
9
66
1
Order By: Relevance
“…This is not nearly sufficient to compensate for systems that show excess L X in Figure 2. In addition, for a subset of our systems, Bitsakis et al (2014) have obtained independent estimates using Herschel data and UVto-IR SED fitting. Their SFRs are systematically lower than ours, which would make our late-type excesses even more severe.…”
Section: Discussionmentioning
confidence: 99%
“…This is not nearly sufficient to compensate for systems that show excess L X in Figure 2. In addition, for a subset of our systems, Bitsakis et al (2014) have obtained independent estimates using Herschel data and UVto-IR SED fitting. Their SFRs are systematically lower than ours, which would make our late-type excesses even more severe.…”
Section: Discussionmentioning
confidence: 99%
“…Model fits to the full multiwavelength data set can provide a consistent constraint to interpret the physical properties of a galaxy, as discussed in Hayward et al (2014). The choice of magphys for this work is based on its wide range of application to reproduce the stellar and dust properties of several galaxy types in several environments, ranging from nearby galaxies and dwarf galaxies to galaxies in a group environment to star-forming galaxies (da Cunha et al 2008;da Cunha & et al 2010a,b;Bitsakis et al 2011Bitsakis et al , 2014Viaene et al 2014). In all these cases, the Bayesian approach in magphys allows the authors to derive statistical constraints (median likelihood estimates) for a set of physical parameters, such as the star formation rate (SFR) or the mass of the dust (MD).…”
Section: Sed Modelling With Magphysmentioning
confidence: 99%
“…Observations have been made across a wide range of the electromagnetic spectrum, from X-rays (Bahcall et al 1984;Sulentic et al 1995;Trinchieri et al 2003;O'Sullivan et al 2009), UV (Xu et al 2005), visible light (Moles et al 1998;Gallagher et al 2001;Fedotov et al 2011), IR (Sulentic et al 2001;Cluver et al 2010;Guillard et al 2010;Natale et al 2010;Suzuki et al 2011;Bitsakis et al 2014) to radio waves (Allen & Hartsuiker 1972;van der Hulst & Rots 1981;Xu et al 2003;Nikiel-Wroczyński et al 2013). These papers have revealed that much of the gas lies either in tidal tails outside the galaxies or in a large intergalactic filament.…”
Section: Introductionmentioning
confidence: 99%